The economic value of storage in renewable power systems - the case of thermal energy storage in concentrating solar plants - Stephan Nagl; Michaela Fürsch; Cosima Jägemann; Marc Oliver Bettzüge (Institute of Energy Economics at the University of Cologne (EWI), 2011)
In this article we analyze the value of thermal energy storages in concentrated solar plants depending on the electricity generation mix. To determine the value from a system integrated view we model the whole electricty generation market of the Iberian Peninsula. Key findings for thermal energy storage units in concentrated solar plants include an increasing value in electricity systems with higher shares of fluctuating renewable generation and a potentially significant role in a transformation to a primarily renewable based electricity system. Due to the relatively high investment costs concentrated solar power plants with or without thermal energy storages are not cost efficient in todays electricity markets. However, expected cost reductions due to learning curve effects and higher fluctuating renewable generation may lead to a comparative cost advantage of concentrated solar power plants with thermal energy storages compared to other renewable technologies.
Keywords: C61; Q40; 330; Fluctuating renewables; value of storage; concentrated solar power; power plant optimization